EFFECT OF DIFFERENT RATES OF BIOCHAR ON NODULATION AND YEILD OF SOYBEAN (Glycine max.L.merill) - SODAH, MUHAMMAD GWAM; Jayeoba, O. J.; Amana, S. M.; Jibrin, I. M. (FUDMA JOURNAL OF SCIENCES, 2022)
The experiments were conducted at the Teaching and Research Farm, Faculty of Agriculture, Nasarawa State University, Shabu-Lafia Campus during 2018 and 2019 cropping seasons to evaluate the effect of different rates of biochar on nodulation and yield of soybean in Lafia, Southern Guinea Savanna of Nigeria. The experiments were laid in randomized complete block design (RCBD) with three replications. Biochar at the rates of 0, 4, 8 and 12 tons/ha was incorporated into ridges at planting. Four seeds of soybean were planted per hole at a spacing of 5cm between plants on four manually prepared ridges of 2 m long spaced at approximately 75cm. The seedlings were thinned to two plants after two weeks of planting (WAP). All data collected were subjected to analysis of variance (ANOVA) using GENSTAT statistical package while least significant difference was used to separate treatment means at 5% level of probability. The results obtained showed that biochar at the rate of 8 tons/ha significantly (p<0.05) produced the highest number of nodules (20.8 and 16.4), recorded the heaviest weight per 100 seeds (16.9 and 14.9g) and grain yield of soybean (1304.0 and 1316.7 kg/ha) in both cropping seasons. The results further revealed that the highest dose of biochar (12 tons/ha) in this study did not necessarily influence and increase any parameter tested except over the control (0.0 tons/ha) in both cropping seasons. Therefore biochar at the rate of 8 tons/ha is hereby considered to be the optimum rate for sustainable soybean production in the study area.